FACTORS ASSOCIATED WITH MALNUTRITION AMONG CHILDREN AGED BELOW 5 YEARS AT KINONI HEALTH CENTRE IV, RWAMPARA DISTRICT. A CROSS-SECTIONAL SURVEY . - BYAMUKAMA , JONAN; NEGESA, JUSTINE (Student’s Journal of Health Research Africa, 2024)
Background. Malnutrition refers to deficiencies excesses or imbalances in a person’s intake of energy and low nutrients. Study objective The specific objectives were to assess the knowledge of caretakers on malnutrition among children, to examine the social demographic factors, and to determine the economic factors associated with malnutrition among children below 5 years at Kinoni Health Center IV, Rwampara district. Methodology A cross-sectional study of 62 respondents was used for the study. The questionnaires were used to collect data and were analyzed using a tally, the data collected was also analyzed using tables and pie charts. Results The majority of respondents were females, residing in rural areas by 72%. Most of them believed that malnutrition was common between the ages of 4 and 5 years. Moreover, they knew that deworming prevents malnutrition. 34.5% had poor knowledge of when to breastfeed the child and 19.4% on the importance of colostrum to the newborn. Only a few 10% stated that they started their supplementary feeds for children before 6 months, while most claimed that nutrients in breast milk alone are no longer adequate for proper child growth. 48.4% replied that poverty leads to inadequate dietary intake, infections, poor hygienic habits, and low education. Many believe that unnecessary high food prices as the highest risk of malnutrition Conclusions. Many of the respondents’ children had good knowledge about malnutrition. The majority were agriculturalists living in rural areas. Most were from poor families where men made decisions on family income expenditure. Recommendations Therefore, the study recommends that health workers continuously health educate the caretakers on how to prevent malnutrition, the requirements to make therapeutic food, how to treat malnutrition in children, and how to feed children under five when they get malnutrition.